Atomistic Insights into Nitrogen-Cycle Electrochemistry: A Combined DFT and Kinetic Monte Carlo Analysis of NO Electrochemical Reduction on Pt(100) - Chun, Hee-Joon; Apaja, Vesa; Clayborne, Andre; Honkala, Karoliina; Greeley, Jeffrey (ACS catalysis, 2017)
Electrocatalytic denitrification is a promising technology for the removal of NO x species in groundwater. However, a lack of understanding of the molecular pathways that control the overpotential and product distribution have limited the development of practical electrocatalysts, and additional atomic-level insights are needed to advance this field. Adsorbed NO has been identified as a key intermediate in the NO x electroreduction network, and the elementary steps by which it decomposes to NH4 +, N2, NH3OH+, or N2O remain a subject of debate. Herein, we report a combined density functional theory (DFT) and kinetic Monte Carlo (kMC) study of this reaction on Pt(100), a catalytic surface that is known to be suitable for the activation of strong covalent bonds, in acidic electrolytes. This approach describes the effects of coverage-dependent adsorbate–adsorbate interactions, water-mediated protonation kinetics and thermodynamics, and transient potential sweeps, on reaction rates and selectivities. The results predict NO stripping curves in excellent agreement with experiments while, at the same time, providing a mechanistic interpretation of observed current peaks. Furthermore, production of NH4 + products is traced to the rapid kinetics of N–O bond breaking in reactive intermediates, whereas rapid hydrogenation of surface N* species prevent competing pathways from forming either N2 or N2O. The combined DFT-kMC methodology thus provides a unique tool to describe the mechanism and energetics of platinum-catalyzed electroreduction in the nitrogen cycle, and this approach should also find application to related electrocatalytic processes that are of technological and environmental interest.